Integrating sensory evaluations in incentivized discrete choice experiments to assess consumer demand for cricket flour buns in Kenya - Mohammed H. Alemu; Søren Bøye Olsen; Suzanne E. Vedel; John Kinyuru; Kennedy O. Pambo (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2016)
In this study, we present one of the first thorough assessments of potential consumer demand for an insect based food product. We assess the demand in terms of Kenyan consumer preferences and willingness to pay for buns containing varying amounts of cricket flour. The novel feature of the study is that it uses an incentivized discrete choice experiment method integrated with sensory experiments intended to reduce any hypothetical bias and to allow participants to acquire experience in terms of tasting the different buns before they make their choices in the choice tasks. We find significant and positive preferences for the buns which contain cricket flour. Interestingly, the bun products with medium amounts of cricket flour are preferred to no or high amount of cricket flour. Finally, we show in a simulated market that the cricket flour based buns are likely to obtain a greater market shares than that of standard buns today.
Keywords: C13; C25; C93; D12; Q01; Q11; Q13; Q18; 330; cricket flour; insect; incentivized discrete choice experiment; taste; willingness to pay